The Demographic Characteristics and Economic Status of Families in Poland : Methods and Empirical Results - Rusnak, Zofia (Charakterystyka demograficzna i status ekonomiczny rodzin w Polsce : metody i wyniki badań, 2009)
The main goal of this paper is to present the results of the empirical research aiming at deciding which variables actually do describe the demographic profile of families for which the estimated Engel’s curve matches the empirical data best. The decision which variables to use in this work was affected - among others - by the way the equivalence scale (defined on the basis of the estimated curve’s parameters) was used as well as by the nature of the available statistical data. The equivalence scales were supposed to: determine the income and expenditure needs of families with children, which would allow the attainment of the economic status of a childless marriage, estimate the costs of keeping children in households characterized by various number of children of different age. The statistical data used for all calculations arc aggregate data related to income and expenses (per capita) from the Polish CSO publications from 1993 to 2004 and unit data from household budget research carried out by the CSO in 2004.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 86-97